2020
DOI: 10.7759/cureus.8609
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Small Cell Carcinoma of the Urinary Bladder

Abstract: Hossain et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Their findings are inconsistent with our experience in this case. Comparable to our findings, Hossain et al reported that SCBC with muscle metastasis treated with a similar therapy achieved at least four months of disease control [ 5 ]. However, only a few cases have reported similar findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Their findings are inconsistent with our experience in this case. Comparable to our findings, Hossain et al reported that SCBC with muscle metastasis treated with a similar therapy achieved at least four months of disease control [ 5 ]. However, only a few cases have reported similar findings.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, combining chemotherapy with immunotherapy has attracted attention as a treatment option for extensive-disease SCLC [ 4 ]. However, few reports have described its efficacy for SCBC [ 5 ]. We report the first case of metastatic SCBC where carboplatin, etoposide, and atezolizumab achieved long-term complete response.…”
Section: Introductionmentioning
confidence: 99%